Spatiotemporal variation in acorn production and damage in a Spanish holm oak (Quercus ilex) dehesa - Perez Izquierdo, L; Pulido, F (Forest Systems; Vol 22, No 1 (2013), 2013)
Aim of study. There is a lack of knowledge about spatio-temporal patterns of acorn production in dehesas, especially regarding the influence of different agents causing acorn damage. We examined the spatial and temporal variability on acorn production and damage in four stands within a dehesa farm in 1997, 1998 and 1999. Area of study. The study was carried out in a 1800 ha dehesa farm of Cáceres province, western Spain. Material and Methods. Acorns were sampled by means of seed traps placed in the canopy of six holm oak trees per stand. Acorn collected in it were counted and assessed for damage by Curculio weevils, Cydia moths and the bacterial pathogen Brenneria quercina . Main results. Mean acorn production for the whole study period was 44.60 acorns m -2 , which did not vary significantly either among stands or among years. The variability among individual trees was very high (0-300 acorns m -2 ). The rate of infestation by Curculio was 7.64 ± 10.72 %, by Cydia was 1.76 ± 3.33 %, whereas 10.29 ± 16.12 % of acorns were infested by Brenneria . We found no significant spatial differences, but the rates of acorn loss by insects varied among years. These rates were independent of annual acorn production and there was no correlation among damages by different pests, except between Curculio and Cydia in two crop years. Research highlights. It can be concluded that acorn crops are synchronized at the within-farm level and that the temporal variation in acorn damages can be independent of crop size. Keywords: Acorn production; Brenneria; Curculio; Cydia; dehesa; Quercus ilex; spatio-temporal variation.
Keywords: acorn production; Brenneria; Curculio; Cydia; Dehesa; Quercus ilex; spatio-temporal variation

Positive cascade effects of forest fragmentation on acorn weevils mediated by seed size enlargement - Bonal, Raul; HERNÁNDEZ, MARISA; ORTEGO, JOAQUÍN; Muñoz, Alberto; ESPELTA, JOSEP M. (Insect Conservation and Diversity, 2012)
Abstract. 1. Today, forest fragmentation is one of the major threats to biodiversity worldwide. In this context, fragmented populations of specialised forest organisms face an increasing risk of extinction because of factors such as local food scarcity. Nonetheless, the role of food availability may differ depending on organism size, which is expected to determine the energy requirements and mobility between fragments. 2. A field study was carried out on Curculio elephas, a forest beetle with low dispersal potential, whose larval development takes place in oak Quercus spp. acorns. 3. For a similar seed crop per tree, acorn size was larger in isolated oaks than in trees located in forest patches. Thus, fragmentation increased local food availability for C. elephas. Larger acorns enabled larval size to increase, a key fitness proxy associated with individual survival, adult size, and potential female fecundity. Indeed, the number of both adults and larvae was higher in isolated trees than in forest patches. 4. In the current scenario of increasing forest fragmentation, the survival likelihood of specialist insects may strongly depend on their ability to adapt to altered environmental conditions. To the best of our knowledge, this is the first study to report on how some forest insects may take advantage of fragmentation-mediated changes to survive in isolated trees. 5. From a conservation perspective, management policies should preserve isolated trees as a source of seeds and fauna for the natural regeneration of forest ecosystems after unproductive farmlands have been abandoned.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn size; Curculio; Forest fragmentation; forest insects; Global change; individual fitness; larval size

Complex selection on life-history traits and the maintenance of variation in exaggerated rostrum length in acorn weevils. - Bonal, Raul; Espelta, Josep Maria; Vogler, Alfried P. (Oecologia, 2011)
Trophic interactions can trigger the development of exaggerated specialized characters and promote morphological diversification. For example, acorn weevils (genus Curculio) present strikingly long rostrums, which are used by females to perforate oviposition holes through the seed coat. Species exhibiting longer rostrums are known to exploit larger acorns, and therefore rostrum length is thought to be subject to selection to match the preferred acorn type. However, rostrum length is strongly correlated with body size, and morphological divergence could result from either selection on rostrum length for optimal food exploitation or from other pressures acting on body size. We collected infested acorns at oak forests where the large Curculio elephas and the small-bodied Curculio glandium co-occur. There were no interspecific differences in adult female body size to rostrum length allometric relationships, and rostrum length is equally correlated with body size in either species. MtDNA-based species identification showed that C. glandium larvae were present within acorns of all sizes, whereas C. elephas larvae were restricted to acorns above a minimum size, irrespective of oak species. Hence, exploitation of large acorns can hardly have triggered rostrum enlargement, as the small sized C. glandium adults (with short rostrums) could perforate and oviposit in both small and large acorns. Rather, increased rostrum length is probably a by-product of the larger body sizes of individuals emerging from bigger acorns, which allow increased larval size and enhance larval survival likelihood. Summarizing, when exaggerated feeding traits co-vary with other body features, interspecific morphological variability may result from contrasting selective pressures acting on these correlated characters.
The following values have no corresponding Zotero field: accession-num: 21674207
Keywords: Body size; Curculio; Ecomorphological diversification; Quercus; Seed size; Trophic segregation

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C J; Tomás Barberán, F a; Espin, J C; López Carrasco, C; Olivares, A; Rey, a I (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
Keywords: Curculio; fat; fatty acid; iberian pig

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C. J.; Tomás Barberán, F. a; Espin, J. C.; López Carrasco, C.; Olivares, A.; Rey, a I. (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
The following values have no corresponding Zotero field: accession-num: 22064301
Keywords: Curculio; fat; fatty acid; iberian pig

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size